Acute Gastrointestinal Bleeding in Olmesartan-Associated Collagenous Gastroduodenitis: A Potential Endoscopic Complication - Rachel Hudacko; Lance Siegel (Case Reports in Gastrointestinal Medicine)
Collagenous gastroenteritis is a rare disease that is known to be associated with the drug olmesartan, an angiotensin II receptor antagonist used to treat hypertension. It is characterized histologically by increased subepithelial collagen deposition with associated inflammation and epithelial injury. Endoscopically, the mucosa appears inflamed and friable and may be nodular or atrophic. We report a case of acute gastric bleeding on direct mucosal contact during endoscopy in a patient with olmesartan-associated collagenous gastroduodenitis to raise awareness of this potential endoscopic complication.